METODE LISTENING TEAM MELVIN L. SILBERMAN DALAM PEMBELAJARAN PENDIDIKAN ISLAM - Ahmad Ma'ruf; Cahyati Khasani (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2020)
The use of methods that are too monotonous and less varied will affect student learning outcomes. Conversely, when a teacher uses a varied and fun method, it is able to develop students' knowledge optimally. According to some education experts, one method that can develop students' knowledge is the listening team method. This learning method is offered by Melvin L Silberman in his book active learning which contains 101 models of active learning strategies including the Listening Team learning method. In this study, the aim of this research is to answer the problem, namely: